Pengasuhan Positif Nenek pada Anak Buruh Migran (Upaya Pembentukan Perilaku yang Matang) - Rahmatullah, Azam Syukur; Syafii, Muhammad Hisyam (Lembaga Yasin AlSys, 2025)
This paper talks about how to take care of a grandmother who is responsible for taking care of the primary caregiver, because the primary caregiver is working as a migrant worker. The purpose of this study is to examine more deeply what efforts grandmothers can make in implementing positive parenting while taking care of their grandchildren. It is hoped that with this research, the results can be used as a role model for positive parenting of a grandmother to her grandchildren, and can be applied by other grandmothers. So that the grandmothers are able to shape the behavior and personality of mature grandchildren. This type of research is qualitative, with the type of approach being content analysis, namely news analysis, journal articles, books, videos and so on focusing on Central Java and Yogyakarta. The results of the study show that positive parenting is actually the main basis for the formation of positive children's character and behavior, besides that it is also the basis for the formation of a mature personality. If the parenting that is sown is not positive, then the child will experience mental and behavioral pain not only in his body but also in his soul and mind. This affects when growing up, children will have an inner disease that will continue to be attached, which in the end cannot be cured. Therefore, positive parenting must be realized, studied and developed by parents and secondary caregivers, in order to be able to create mature and positive personalities and characters of children and grandchildren.